Study of Carbonaceous and Nitrogenous Pollutant Removal Efficiencies in a Hybrid Membrane Bioreactor - Victor S. Ruys; Kamel Zerari; Isabelle Seyssiecq; Nicolas Roche (Journal of Chemistry)
A hybrid membrane bioreactor (HMBR) comprises activated sludge (free biomass), a biofilm (supported biomass), and a membrane separation. A laboratory pilot-scale HMBR was operated for seven months with high organic loads of both carbonic and nitrogen pollutants. Several experiments were conducted to investigate the influence of the height of the packing bed (27 cm, 50 cm, and 0 cm) and the effect of the concentration of dissolved oxygen (DO) on the organic removal rate, total nitrogen removal rate (TN), and ammonium removal. The organic removal rate was always >95% and mostly >98%. The NH4+-N and TN removal rates were directly related to DO. NH4+-N removal rate reached 100% and was mostly >99% with a concentration of DO > 0.1 mg/L, whereas the NO3--N removal rate was differentially affected depending on the level of DO. The removal rate increased when the concentration of DO was optimal for simultaneous nitrification and denitrification, which was between 0.1 and 0.5 mg/l, and the TN removal rate was consequently high. The removal rate decreased when DO was high and denitrification was consequently low thereby reducing the TN removal rate. This implies that high levels of DO (>1 mg/L) limit the denitrification process and low levels of DO (<0.1 mg/L) limit the nitrification process and hence total nitrogen removal in the bioreactor.